Tourism and Tradition in the Himalayas: Divergent Narratives from Western and Nepalese Travelers - Sharma, Khum Prasad (Universitas Brawijaya, 2025)
The Himalayas, renowned for their majestic landscapes and rich cultural heritage, have long captured the imagination of travelers and scholars. However, the narratives surrounding tourism in this region reveal contrasting perspectives. Western travel narratives often romanticize the Himalayas as a space for adventure, spiritual awakening, and personal transformation, while Nepalese narratives emphasize the cultural, communal, and environmental significance of the region. This study aims to explore these divergent narratives, examining how tourism influences cultural representation, identity, and preservation in the Himalayas. The research adopts a qualitative and textual analysis approach, analyzing key travel literature by Western authors such as H.W. Tilman and Peter Matthiessen alongside Nepalese voices like Karna Shakya and Takaraj Gurung. Employing postcolonial theory, discourse analysis, and cultural sustainability as theoretical frameworks, the study identifies thematic patterns such as adventure, commodification, ecological sustainability, and cultural authenticity. The research highlights the interplay between these narratives and their implications for tourism practices. The findings reveal that Western accounts often romanticize the Himalayas as an exotic landscape, marginalizing the socio-cultural realities of local communities. Conversely, Nepalese narratives critique the commodification of traditions and advocate for sustainable tourism practices that prioritize cultural preservation and environmental stewardship. These perspectives underline the necessity of integrating local voices into global tourism discourses to foster more balanced and inclusive narratives. In conclusion, the study underscores the importance of bridging the gap between Western romanticism and Nepalese realism, recommending further research that includes diverse voices and interdisciplinary approaches. Such efforts can contribute to sustainable tourism models that respect cultural heritage, empower local communities, and ensure ecological sustainability in the Himalayas.